Essential complicity of perforin-granzyme and FAS-L mechanisms to achieve tumor rejection following treatment with anti-CD137 mAb. Issue 1 (29th May 2013) - Morales-Kastresana, Aizea; Catalán, Elena; Hervás-Stubbs, Sandra; Palazón, Asis; Azpilikueta, Arantza; Bolaños, Elixabet; Anel, Alberto; Pardo, Julián; Melero, Ignacio
Abstract : Background: Treatment with agonist anti-CD137 (4-1BB) immunostimulatory monoclonal antibodies elicits complete tumor regressions in a number of transplanted hematological and solid malignancies in mice. Rejection is mainly dependent on cytotoxic T lymphocytes (CTL) and IFNγ, although a role for NK cells and dendritic cells has been observed in some tumor models. Rejection of EG7-derived thymomas has been shown to be CTL-dependent but not NK-dependent. Findings: In this therapeutic setting, we show that both the perforin-granzyme and FasL effector systems are readily expressed by CD8 + T lymphocytes infiltrating the EG7 lymphomas which are undergoing rejection. Using knock-out mice, we demonstrate that both effector cytolytic systems are involved in the execution of complete immune rejections against EG7 established tumors. In accordance, EG7 tumor cells were susceptible in vitro to both killing mechanisms acting in a synergistic fashion. Conclusions: CD137-elicited rejection of EG7-derived tumors involves the interplay of at least two final effector cytolytic mechanisms that act in cooperation.